Conflicting Philosophies and International Trade Law Worldviews and the WTO - Burkard, Michael (Philosophy, Public Policy, and Transnational Law, 2018)
This book reveals how conflicting worldviews are at the root of public controversies on policy and trade issues. It highlights the particularly controversial disputes at the level of the World Trade Organization in the case of regulating beef-hormones and GMOs, aiming to show how negotiators of international agreements, members of dispute settlement bodies, and policy makers in general could have recourse to concepts of other disciplines such as epistemology and philosophy in order to address deadlocked legal disputes. Ultimately, the book is a manifesto for independent and critical research. .